Optimal Dynamic Asset Allocation with Transaction Costs - Collin-Dufresne, Pierre,Daniel, Kent,Sağlam, Mehmet (National Bureau of Economic Research, 2024)
A number of papers have solved for the optimal dynamic portfolio strategy when expected returns are time-varying and trading is costly, but only for agents with myopic utility. Non-myopic agents benefit from hedging against future shocks to the investment opportunity set even when transaction costs are zero (Merton, 1969, 1971). In this paper, we propose a solution to the dynamic portfolio allocation problem for non-myopic agents faced with a stochastic investment opportunity set when trading is costly. We show that the agent's optimal policy is to trade toward an
Hardcopy version available to institutional subscribers
Keywords: Arbeitspapier; Graue Literatur; Hedging; Portfolio-Management; Transaktionskosten; Theorie; Portfolio Choice; Investment Decisions; Asset Pricing; Trading Volume; Bond Interest Rates